Changes in the Shoe-making Profession as a Legacy Transferred From Father to Son: Denizli-Yeşilyuva Sample - Türkan Erdoğan; Şirin Eda Uyanık (Journal of Economy Culture and Society)
In this article, industrial developments in the shoe-making profession of continued from the past to the present in the Yeşilyuva neighbourhood (formerly a village in Acipayam district) of the Denizli province, changes inoccupational division of labor, production place and technique, transfer of the profession from father to son, etc. were discussed. In this study, using participatory observation and semi-structured interview techniques among qualitative research techniques, the objective was to learn from individuals about their attitudes towards the profession, their professional modes of production, what happened during the professional transfer phase, and how the division of labor was, and to determine how it has changed over time. According to the research findings, the shoe-making profession, which used to be a craft performed with simple tools and arm strength, was affected by the factorization in the city. After the industrial development, the production of shoes in Yeşilyuva began to be based on the mechanization of the production of shoes in Yeşilyuva, especially during 1990s. Industrial developments and changes created by mechanization over time have led to some changes in the master-apprentice relationship, and in the work and task sharing of factory workers. There are now breaks in the transfer of the shoe-making profession from father to son.